POMNAS XVI THEME SONG "RAIH PRESTASI" COMPOSING PROCESS USING DIGITAL AUDIO WORKSTATION APPLICATION `CUBASIS` - Andriyanto, R.M.Aditya (Jurnal Penelitian Musik, 2021)
This research study the process of composing POMNAS XVI theme song "Raih Prestasi" using Digital Audio Workstation Application `Cubasis`. It is meant to improve knowledge about composing song process and the ability of using software/DAW application as one of digital literacy in 21th Century music education. This research using qualitative method and explorative approach, describing the process of composing the music using DAW Application `Cubasis` and measure the effectiveness and efficiency in using Cubasis to compose music. The results of this study shows that in recent years some of the application developer start to optimize iPad to be used as a portable recording gear. "Raih Prestasi" POMNAS XVI Theme Song composed using DAW `Cubasis` on iPad and in relatively short time (8 days), the whole composing process of this song could be done with good quality. This result can inspire content creator and home recording user to switch to mobile/portable recording technology.